Anti-tax avoidance law in Malaysia : a comparative study - Kuek Tee Say (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2012)
Tax evasion and avoidance pose a serious problem for the tax system and the response by the governments is to control it. Tax avoidance is used to denote the reduction of tax liability through legal means whereas tax evasion involves non payment of tax through violation of law. The focus of this thesis is on tax avoidance rather than on tax evasion. It is important to understand the concepts of “tax evasion”, “tax avoidance” and “tax mitigation” in the study of tax avoidance. With these distinctions between evasion, avoidance and mitigation, the problem of tax avoidance and its causes can be identified in the countries under study. This research examines the legislative, judicial and administrative measures adopted by Malaysia, UK, Australia and India to tackle tax avoidance and evasion. The question this thesis has to address is whether current methods of dealing with tax avoidance by Malaysia are adequate and satisfactory and what, if any, other measures might be taken based on the experiences of UK, Australia and India. A quick answer is “yes” but further improvements to the general anti-avoidance rule (section 140 of the ITA 1967) should be considered based on the Australian anti-avoidance rule and certain additional measures from the countries under study can also be adopted. It is not possible to eradicate tax avoidance totally. Instead, there is a need to find a right balance so that taxes are not unduly avoided and the legitimate interests of taxpayers in their commercial and private affairs are not unnecessarily hindered. On the payment of zakāt, there should be no avoidance because of its spiritual significance in Islam as the third pillar. In modern times, various sanctions and administrative measures are used to compel payment of zakāt. In cases where Muslims are required to pay both zakāt and income tax, a rebate of the payment of zakāt against tax payable should be given as an incentive to pay zakāt.